Compared outcomes of femoral shaft fracture treatment in school-age children in Sub-Saharan Africa: Primary open reduction and intramedullary K-wire fixation versus traction followed by spica cast - Jean Baptiste Yaokreh; Moufidath Sounkéré-Soro; Samba Tembely; Yapo Guy-Serge Kouamé; Audrey Helen Thomas; Thierry-Hervé Od; Bertin Dibi Kouamé; Ossénou Ouattara (Wolters Kluwer Medknow Publications, 2021)
Background: Elastic stable intramedullary nailing has become the treatment of choice for femur shaft fractures in school-age children in developed world. However, in the sub-Saharan Africa, this management is still challenging because of the lack of fluoroscopy in more hospitals. We performed either primary open reduction and intramedullary K-wire fixation (PORIKF) or conservative treatment. The aim of this study was to compare the clinical and functional outcomes of these two procedures employed. Patients and Methods: This retrospective study included 62 children with 64 fractures (10 years on an average; range: 6-15 years) treating for femoral shaft fractures either by PORIKF (n = 21; 23 fractures) or skin traction followed by spica cast (n = 41) between 2008 and 2017. Outcomes were assessed using Flynn criteria. Comparisons were made by Fisher and Student's t-test with a significant P < 5%. Results: Outcomes were satisfactory in 21 cases (91%) in the PORIKF group compared with 32 (78%) in the conservative group (P = 0.3012). The average hospital stay was 18.6 days in the PORIKF group, whereas it was 20 in the conservative group (P = 0.0601). The mean time for bone union was 13.9 weeks in the PORIKF group and 13.2 weeks in the conservative group, (P = 0.4346). There was a statistically significant difference between the two groups in terms of major complications (P = 0.0177). One patient had osteomyelitis in the PORIKF group. Unacceptable shortening >2 cm was observed only in the conservative group. The average time to return to daily activities was 30 days shorter in the PORIKF group when compared to conservative group (P < 0.05). Conclusion: PORIKF provides better results than conservative treatment. Open reduction did not increase the rate of infectious complication.